The Speech Act of Cartoon Movie: Spongebob Squarepants’ The Movie - Ima Frafika Sari (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
This research aims to reveal: the types of speech acts used by the main character in “Spongebob Squarepants’ the movie and the previous studies in speech act analysis for knowing the way of the directives of speech act appears. It employed descriptive qualitative research in the explaining of speech acts types used by the main character. There is still a lack of research about the analysis of speech act categories in cartoon movie or animation movie, it is substantial to be carried out. The finding of this research is the directives speech act is the most frequently in SpongeBob SquarePants the movie with data 118 or 44,36% from a total of 266 or 100% of the whole data. Then, the similarity data found in the three journals about analysis of speech act with data that the directives speech act is the highest utterance in a cartoon movie.